2018
DOI: 10.1177/0003319718756732
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Sex- and Gender-Centered Prevention and Management of Cardiovascular Disease: Implications of Genetic, Metabolic, and Environmental Paths

Abstract: The recognition of cardiovascular disease (CVD) as a "male" privilege has been a commonly held concept. However, emerging data describe another reality. Heterogeneities have been convincingly demonstrated regarding CVD manifestations, risk factor burden, and prognosis between males and females. The aim of the present narrative review was to highlight sex- and gender-related discrepancies in primary and secondary CVD prevention, underscoring plausible underlying mechanisms. Manifestation of CVD in women is char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 77 publications
1
13
0
Order By: Relevance
“…The present study also demonstrated that the generic clopidogrel formulation is equally effective in different subgroups, including different genders, within the studied population. Stratified analyses with gender as strata are important to confirm the drug efficacy against major events as well as its safety [ 25 ]. In the present work, both the statistical (in terms of p for interaction) and the clinical (in terms of stratified risk analysis) gender–treatment interaction were evaluated, but no significant differences were observed ( Figures 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also demonstrated that the generic clopidogrel formulation is equally effective in different subgroups, including different genders, within the studied population. Stratified analyses with gender as strata are important to confirm the drug efficacy against major events as well as its safety [ 25 ]. In the present work, both the statistical (in terms of p for interaction) and the clinical (in terms of stratified risk analysis) gender–treatment interaction were evaluated, but no significant differences were observed ( Figures 1 and 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding that men with dementia use more lipid-lowering therapies suggests that cardiac comorbidities are more common in community-dwelling men with dementia 63 but may also reflect known differences in cardiovascular comorbidity identification and treatment between men and women in the general population. 68…”
Section: Discussionmentioning
confidence: 99%
“…7,8 In this context, women are to wait longer between seeking and receiving medical advice. 9 On the other hand, female patients are susceptible to underdiagnosis, inappropriate therapeutic decisions, or even remaining untreated, as physicians usually underestimate their risk burden. 10,11 Therefore, it is considered that the time has come for a sustained effort and commitment to encompass in the women's health agenda tailor-made strategic plans regarding the effective prevention and management of CVD.…”
Section: Introductionmentioning
confidence: 99%